Knowledge of HIV/AIDS and Perceived Contraceptive Access among Indian Adolescents: Evidence from UDAYA Data - S Prinitha; P Jose, Tony (National Journal of Community Medicine, 2025)
Background: Access to contraceptive methods among adolescents is a critical factor in improving sexual and reproductive health outcomes. The study investigated the determinants of perceived contraceptive access among Indian adolescents by exploring role of HIV/AIDS knowledge, condom awareness, health facility accessibility, and socio-demographic variables, while analysing gender differences. Methodology: Data from Understanding the Lives of Adolescents and Young Adults (UDAYA) – Wave 2 (2018-19) included 2,716 adolescent boys and 10,425 adolescent girls, both aged 15–19 years. Descriptive analysis, Chi-square test and multivariate logistic regression were employed. Results: Significant gender disparities exist across all variables (p<0.001), particularly in health facility accessibility (χ²=2200), condom awareness and HIV/AIDS knowledge, and perceived contraceptive access. Multivariate analysis revealed condom awareness most strongly associated with perceived contraceptive access for both boys (OR=2.69, 95%CI:2.07-3.50) and girls (OR=1.45, 95%CI:1.32-1.60). HIV/AIDS knowledge and health facility access also significantly increased perceived contraceptive access odds in both groups. Socioeconomic factors played a crucial role in determining perceived contraceptive access. Conclusion: Enhancing adolescents perceived contraceptive access requires improving HIV/AIDS knowledge, condom awareness, and healthcare accessibility. Especially for teenagers from different socioeconomic strata, policy interventions need to focus on removing barriers to healthcare access.